Work hardening discrepancy designing to strengthening gradient nanotwinned Cu. (August 2021) - Wan, Tao; Cheng, Zhao; Bu, Linfeng; Lu, Lei
Abstract: This study investigates the mechanical behaviors of sandwiched gradient nanotwinned (GNT) Cu designed by only changing the soft component in the central layer with a fixed hard component at its surface. We found that as the work hardening discrepancy of components increases, both the strengthening and work hardening of GNT Cu increase simultaneously, producing a better strength-ductility synergy compared to their freestanding components. The optimized mechanical properties are results of the promoted strain delocalization, prolonged elastic-plastic transition, and larger strain gradient, which induces more geometrically necessary dislocations (GNDs) at the interfaces. Graphical abstract: Image, graphical abstract